Evaluasi Level Kognitif dan Kepatuhan Kunjungan Lansia pada Pos Pembinaan Terpadu (Posbindu) di Masa Pandemik Covid-19: Studi Cross Sectional - Esti Nur Janah; Sefatul Fahmi (Journal of Bionursing, 2022)
Posbindu is a form of community service in carrying out early detection and monitoring of risk factors for major non-communicable diseases which is carried out in an integrated, routine, and periodic manner involving the role of the community under the guidance of the Puskesmas. The pandemic period made all mass activities limited so that elderly visits to posbindu also decreased. The decrease in elderly visits has led to an increase in uncontrolled non-communicable diseases. This study aims to determine the relationship between the level of knowledge of the elderly about non-communicable diseases with the level of adherence to Posbindu visits in the Pandemic Period. This type of research is a correlational study with a cross sectional approach (cross-sectional). The population of this study was Paguyangan Village residents aged 65 to 80 years in the Paguyangan Community Health Center working area with a total of 437 people. The sample used was 37 people using the Slovin formula. The research instrument used a knowledge questionnaire about non-communicable diseases consisting of 27 questions and a questionnaire about adherence to posbindu visits consisting of 10 questions. Data analysis used univariate analysis and bivariate analysis. The results of the study stated that there was a significant relationship between the knowledge of the elderly and the compliance of the elderly visiting posbindu with p value = 0.000 <0.05. The better the knowledge level of the elderly, the more obedient they are to visiting posbindu. Medical officers must be more intensive in providing health services in posbindu because the level of knowledge and compliance of the elderly is already good. The results of this study can be used as a measure to further improve the quality of posbindu services in Paguyangan Village. This research can also be used as the basis for the idea of ​​providing nursing innovations for the readiness to increase knowledge of the elderly and nursing interventions that can be carried out by the elderly independently by involving the family.